Putting Raters in Ratees' Shoes: Perspective Taking and Assessment of Creative Products. Issue 3 (3rd July 2017) - Han, Jiantao; Long, Haiying; Pang, Weiguo
Abstract : This study reported 2 experiments that studied the effect of perspective taking on assessment of creative products by using human raters. Forty responses of 2 alternative uses tasks (AUTs) and 15 alien stories generated by 6th-grade students were used as assessment materials. Undergraduate students as the novice raters assessed the products under 3 experimental conditions: assessing without any information of the ratees, assessing only with age information of the ratees, and assessing with age information and taking the perspective of the ratees. Results of Experiment 1 showed significant differences in creativity ratings between group 1 and 2. But no significant difference was found between group 2 and 3. In Experiment 2, raters in group 1 used objective perception and raters in group 3 were asked to take the perspective for more time. Raters in group 3 assigned higher ratings than the other 2 groups but no difference was found between group 1 and 2. Overall, the results showed the effect of perspective taking on assessment of creative products. Possible mechanisms of the effect and implications for creativity assessment and creativity teaching practice were discussed.